Posture and posturology, anatomical and physiological profiles: overview and current state of art - Carini, Francesco; Mazzola, Margherita; Fici, Chiara; Palmeri, Salvatore; Messina, Massimo; Damiani, Provvidenza; Tomasello, Giovanni (Acta Biomedica Atenei Parmensis, 2017)
Background and aim of work: posture is the position of the body in the space, and is controlled by a set of anatomical structures. The maintenance and the control of posture are a set of interactions between muscle-skeletal, visual, vestibular, and skin system. Lately there are numerous studies that correlate the muscle-skeletal and the maintenance of posture. In particular, the correction of defects and obstruction of temporomandibular disorders, seem to have an impact on posture. The aim of this work is to collect information in literature on posture and the influence of the stomatognathic system on postural system. Methods: Comparison of the literature on posture and posturology by consulting books and scientific sites. Results: the results obtained from the comparison of the literature show a discrepancy between the thesis. Some studies support the correlation between stomatognathic system and posture, while others deny such a correlation. Conclusions: further studies are necessary to be able to confirm one or the other argument.